Engagement in Games: Developing an Instrument to Measure Consumer Videogame Engagement and Its Validation. (31st January 2017) - Abbasi, Amir Zaib; Ting, Ding Hooi; Hlavacs, Helmut
Abstract : The aim of the study is to develop a new instrument to measure engagement in videogame play termed as consumer videogame engagement. The study followed the scale development procedure to develop an instrument to measure the construct of consumer videogame engagement. In this study, we collected the data in two different phases comprising study 1 (n = 136 ) and study 2 (n = 270 ). We employed SPSS 22.0 for exploratory factor analysis using study 1 respondents to explore the factors for consumer videogame engagement and reliability analysis. Results of EFA resulted with six-factor solution. We further used SmartPLS 3.0 software on study 2 respondents to further confirm the six-factor solution as reflective measurement model on the first-order level, and three second-order formative constructs on the second-order or higher-order level as formative measurement model. Results of the reflective measurement model and formative measurement model evidenced that consumer videogame engagement has strong psychometric properties and is a valid instrument to measure engagement in videogame play. Results also confirmed that consumer videogame engagement is a multidimensional construct as well as a reflective-formative construct. The study is unique in its investigation as it develops an instrument to measure engagement in videogame play which comprises the cognitive, affective, and behavioral dimensions.